Buckling Test of Composite Cylindrical Shells with Large Radius Thickness Ratio - Atsushi Takano; Ryuta Kitamura; Takuma Masai; Jingxuan Bao (Applied Sciences, 2021)
A buckling test of composite cylindrical shells with a radius–thickness ratio (r/t) = 893 under axial compression was conducted to investigate the effects of the radius–thickness ratio (r/t). It is known that the buckling load of cylinders shows large differences and scatter between theory and experiment. The ratio of the experimental buckling load and theoretical buckling load is called the knockdown factor (KDF). Many investigations have been conducted to find the cause of the degradation and scatter in the KDF, but as yet, no cause has been found. In 1968, NASA’s buckling design criterion, NASA SP-8007, gave an empirical KDF curve that decreased with the increasing r/t (up to 2000) for metal cylinders. The same curve has been applied to composite cylinders. Recently, Takano derived a flat lower-bound KDF in terms of A- and B-basis values (99% and 90% probability with a 95% confidence level) through a statistical analysis of experimental buckling loads. The result, however, based on experimental results up to r/t = 500 and, thus, the dependency on a large range of r/t, is not clear. Thus, the authors focused on a larger range of r/t. Cylindrical shells made from carbon fiber-reinforced plastic (CFRP) were tested. The nominal radius, thickness, and length were r = 100.118 mm, t = 0.118 mm, and L = 200 mm and, thus, the r/t = 848 and length-to-radius ratio (L/r) = 2.0. Shape imperfections were also measured by using in-house laser displacement equipment. The buckling load was slightly affected by the r/t, but the reduction in the KDF was insignificant.